Identifying hub genes, key pathways and key immune-related genes in Peyronie’s disease by integrated bioinformatic analysis - Cui, Yuanshan; Chen, Lili; Wang, Xiaofeng; Yu, Luxin; Wu, Jitao (Frontiers in Pharmacology, 2022)
Scarring diseases, such as Peyronie’s disease (PD), usually lead to disorders in the immune system. Previous studies suggested that the PD process was regulated by immune signaling. However, the pathogenetic mechanism remains incompletely characterized. This article used bioinformatic approaches to identify hub genes, key pathways and key immune-related genes that play essential roles in PD pathogenesis. Two Gene Expression Omnibus (GEO) datasets, GSE126005 and GSE146500, were used to analyse the transcriptional profiling in both PD and normal samples. R software was applied to examine the difference in the expression of hub genes and key immune-related genes. The candidates for hub genes were further validated through protein–protein interactions (PPIs), gene correlation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. In addition, candidate miRNA‒mRNA pairs were functionally assessed. A total of 39 candidate genes were identified, the expression levels of which in PD fibroblast cells were different from those in normal cells (16 showed reduced expression in PD and 21 candidates overexpressed in PD). We found that these genes could interact with each other through PPI analysis. According to the functional enrichment analysis, the candidates may regulate some major biological processes, including cytokine‒cytokine receptor interactions and the JAK-STAT signaling pathway. IL6, IL21R, IFNE, CXCL2, EGF, and ANGPTL5 were identified as key immune-related genes. The findings may help understand the role of immunologic contributors in PD, thus shedding light on the development of more effective strategies to prevent and treat this kind of disease.